Preparation method of dianion catalyst and application of dianion catalyst in catalytic degradation of polyurethane material
Through the synergistic action of the bianionic catalyst, the problem of efficient depolymerization and recycling of polyurethane soft foam is solved, and the degradation rate and quality improvement is achieved. It is suitable for the preparation of polyurethane soft foam and has industrial application potential.
Patent Information
- Application Number
- CN202411183355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to efficiently depolymerize and recover high-quality polyurethane soft foam, and the traditional method has a high reaction temperature and the catalyst has no significant effect on improving the reaction rate, resulting in waste of resources and environmental pollution.
The bianionic catalyst is used to enhance the offensive ability of the nucleophilic reagent and the positive electrical properties of the carbamate bonds through the synergistic effect of metal ions with azacyclic compounds and amine compounds, reduce the reaction temperature, and improve the degradation rate and degree.
The degradation rate and degree of polyurethane are significantly improved, and the quality of the prepared recycled polyol is close to the raw materials. It is suitable for the preparation of polyurethane soft foam, with good activity and high temperature stability, and has industrial application prospects.
Smart Images

Figure CN119303631A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical catalytic degradation and recovery of waste polyurethane materials, and in particular to a preparation method of a double anion catalyst and application thereof in catalytic degradation of polyurethane materials. Background Art
[0002] The annual consumption of polyurethane products in my country has exceeded 15 million tons, and the annual waste production is as high as 400,000 tons. They are widely used in aerospace, daily household, transportation and other fields. Because of their insoluble and infusible cross-linked structure, they are difficult to recycle and reuse. Waste polyurethane can only be landfilled, incinerated or crushed and compacted for the production of low-end products, with a recovery rate of less than 10%, causing serious ecological and environmental problems and waste of resources. In addition, most widely used polyurethane materials are mixed, with complex structures and variable compositions, which bring great challenges to chemical recycling.
[0003] At present, the chemical depolymerization methods of waste polyurethane mainly include alcoholysis, acidolysis, aminolysis, hydrolysis and enzymolysis. The common goal of these methods is to depolymerize polyurethane into polymerizable polyols, thereby realizing the recycling of resources and the treatment of non-depolymerizable waste. However, for polyurethane soft foams with high recycling quality requirements and large quantities, there is a lack of efficient depolymerization and recycling technology. The invention patent with publication number CN201910863314.7 discloses a method for preparing polyether polyols by hydrothermal catalytic degradation of waste rigid polyurethane materials. The method uses catalytic solvent thermal technology to catalytically degrade and prepare polyether polyols. The catalyst used does not need to be recovered and remains in the reaction product for use as a catalyst for further synthesis of polyurethane materials. However, the method requires a high temperature (180-240°C), and the most important thing is that the method is limited to rigid polyurethane foams. The invention patent with publication number CN201710649420.6 discloses a method for acidolysis of polyurethane soft foam waste to produce polyols. The invention uses solid acid catalysts, liquid acid catalysts, infiltration acid catalysts, cation exchange resins, and metal salt acid catalysts to achieve the degradation of polyurethane soft foam waste. However, the reaction time of this method requires 9 hours or more, and the reaction temperature requires a relatively high temperature (230°C-250°C). The catalyst has no significant effect on increasing the reaction rate and reducing the reaction activation energy.
[0004] In summary, to achieve green recycling of high-quality polyols, it is necessary to clarify the degradation mechanism of polyurethane, develop key polyurethane degradation catalysts, and use catalytic technology to activate carbamate bonds at the source to enhance the offensive ability of nucleophilic reagents, thereby reducing the reaction temperature and avoiding the production of harmful by-products such as aromatic amines. At the same time, the degree of reaction is increased to improve the quality of recycled polyols. Summary of the invention
[0005] The present invention aims to provide a preparation method of a double anion catalyst and its application in catalytic degradation of polyurethane materials. The catalyst is achieved through the synergistic effect of two aspects: on the one hand, the amine compound enhances the attacking ability of the nucleophilic agent itself; on the other hand, the complex formed by the metal ion and the nitrogen heterocyclic compound enhances the positive charge of the carbonyl carbon on the carbamate bond, making it more easily attacked by the nucleophilic agent, thereby improving the degradation rate and degree. The basic physical properties of the recycled polyol obtained by degradation by the catalyst, such as hydroxyl value, amine value, viscosity, etc., are basically equivalent to those of the raw material polyol, and can partially replace the raw material polyol for the preparation of polyurethane soft foam.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a dianionic catalyst comprises the following steps:
[0008] 1) dissolving a metal salt in deionized water to prepare a metal salt solution;
[0009] 2) taking a nitrogen heterocyclic compound containing a hydroxyl group or an amino group as a substrate in a reactor, adding a metal salt solution dropwise to the reactor, and placing the reactor at 60° C. to 150° C. for condensation reflux for 1 to 8 hours;
[0010] 3) adding an amine compound dropwise to the reactor after condensation and reflux in step 2), reacting for 2-5 hours after the addition is complete, and performing vacuum filtration after the reaction is complete to obtain a filtrate;
[0011] 4) evaporating the filtrate obtained in step 3);
[0012] 5) Drying the product obtained in step 4) to obtain a dianionic catalyst.
[0013] In step 1), the metal salt is one or more of zinc acetate, magnesium acetate, zinc nitrate, cadmium nitrate, nickel nitrate and cobalt nitrate.
[0014] In step 2), the nitrogen heterocyclic compound containing hydroxyl or amino group is one or more of 4-(hydroxymethyl)imidazole, 2-hydroxymethyl-1-methylimidazole, 6-(hydroxymethyl)pyridine-3-ol, 3,4-bis(hydroxymethyl)furan, and 6-hydroxymethylquinoline.
[0015] In step 2), the metal salt solution is slowly added dropwise to the reactor, and the time for slowly adding the metal salt solution dropwise is 20-40 minutes.
[0016] In step 2), the mixture is placed at 100° C.-150° C. for condensation reflux for 1-4 hours.
[0017] In step 3), the amine compound is one or more of phenylethylamine, triphenylguanidine, tetramethylguanidine, and sulfaguanidine.
[0018] In step 3), the amine compound is added dropwise to the reactor after condensation and reflux in step 2), and the reaction is carried out for 2-3 hours after the addition is completed. After the reaction is completed, vacuum filtration is performed to obtain a filtrate.
[0019] The molar ratio of the nitrogen heterocyclic compound containing hydroxyl or amino group, the metal salt and the amine compound is 0.3-1: 0.3-1.5: 0.5-1.
[0020] In step 4), the filtrate obtained in step 3) is treated on a rotary evaporator at 50-60° C. for 1-2 hours;
[0021] In step 5), the product obtained in step 4) is placed in a forced air oven at 80-90° C. and dried for 12-24 hours.
[0022] Specifically, a dianionic catalyst for catalytic degradation of polyurethane materials is synthesized, and the synthesis method is as follows:
[0023] Take a certain amount of metal salt and dissolve it in deionized water to prepare a metal salt solution for use. Take a certain amount of nitrogen heterocyclic compound containing hydroxyl or amino group in a three-necked flask as a substrate, place it under 60℃-150℃, and at the same time, use a constant pressure dropping funnel to slowly drip the metal salt solution prepared in the previous step, and condense and reflux for 1-8 hours after the dripping is completed. Subsequently, slowly drip a certain amount of amine compound, and react for 2-5 hours after the dripping is completed. After the reaction is completed, vacuum filtration is performed to obtain a filtrate. Subsequently, a rotary evaporator at 50-60℃ is used for treatment for 1-2 hours to remove moisture and unreacted compounds. Finally, the sample is placed in a blast oven at 80-90℃ and dried for 12-24 hours to obtain the final product.
[0024] A double anion catalyst for catalytic degradation of polyurethane materials. The degradation method used in this article is our previously authorized patent-a multi-stage degradation method (a method for efficiently and controllably degrading polyurethane foam to recover polyether polyols, patent number: ZL 2021 1 0931533.1; a method and device for degrading and recovering waste polyurethane foam: ZL2022 1 1054512.7).
[0025] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of dianion catalyst to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 140-180°C for 15 minutes. Next, increase the speed of mechanical stirring and add 100g of waste polyurethane foam fragments to the three-necked flask by continuous feeding. After the waste polyurethane foam fragments disappear completely, add 50g of polyether polyol, continue stirring for 1-3 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 1-3 hours until the basic physical properties of the degradation product do not change significantly.
[0026] The catalyst of the present invention is not limited to the degradation of a multi-stage degradation system, and common methods such as acidolysis, alcoholysis, and aminolysis can all produce beneficial effects.
[0027] The synthesis theory of the present invention is based on the fact that metal ions and hydroxyl groups easily form coordination, and amino groups easily form complexes with metal ions. Therefore, the catalyst of the present invention uses metal ions to coordinate or complex with multiple nitrogen heterocyclic compounds and amine compounds, and finally forms a catalyst system with metal ions as the core and coordinated or complexed with dianions.
[0028] The degradation mechanism of waste polyurethane is that the nucleophilic reagent attacks the positively charged carbonyl carbon cation on the carbamate bond, reaction formula (1)
[0029] The mechanism of catalytic degradation of waste polyurethane in the present invention is:
[0030] a. Amine compounds will react with metal M + The complex is formed by complexation. At a certain temperature, the complex bond can be broken to form free AZ-OM + Among them, R-NH2 can provide an alkaline environment for the system, enhancing the ability of nucleophiles to attack the carbonyl carbon on the carbamate bond; on the other hand, R-NH2 itself can also act as a nucleophile and further attack the carbonyl carbon on the carbamate bond.
[0031] b. Free AZ-OM + It represents the complex formed by the coordination of metal ions and nitrogen heterocyclic compounds. + As a catalytic center, it attracts the hydroxyl or amino group on the nucleophile (degradant) and the carbonyl oxygen on the carbamate in the reaction, so that the nucleophile (degradant) and the carbamate bond are simultaneously bound to M. + On the other hand, M +It will attract electrons on the carbonyl group, making the carbonyl carbon more positively charged and more easily attacked by nucleophilic reagents (degradants). At the same time, AZ on the complex has a very strong electron-withdrawing effect, which can greatly enhance the M + catalytic effect.
[0032] The catalyst designed by the present invention not only enhances the attacking ability of the nucleophilic reagent itself through the synergistic effect of the above two aspects, but also enhances the positive charge of the carbonyl carbon on the carbamate bond, making it easier to be attacked by the nucleophilic reagent, reaction formula (2).
[0033]
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] (1) The catalyst of the present invention can significantly improve the degradation rate and degree of degradation during the degradation of waste polyurethane through the synergistic effect of different components.
[0036] (2) The catalyst prepared by the present invention has a simple preparation method, exhibits good activity and high temperature stability, and has a certain industrial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The synthesis equation and product of ZnA2 in the present invention are 1 H NMR spectra;
[0038] Figure 2 is the structural formula of ZnA2;
[0039] Figure 3 This is the data graph of polyurethane foam rebound rate;
[0040] Figure 4 This is the data graph of 50% permanent compression deformation rate of polyurethane foam;
[0041] Figure 5 This is a data chart of 75% permanent compression deformation of polyurethane foam. DETAILED DESCRIPTION
[0042] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0043] Unless otherwise specified in the present invention, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0044] Example 1
[0045] Take 1.2 mol of magnesium acetate and dissolve it in deionized water to prepare a magnesium acetate solution for use. Take 1 mol of 3,4-bis(hydroxymethyl)furan as a substrate in a 500 ml three-necked flask and place it at 150 ° C for condensation reflux. At the same time, use a constant pressure dropping funnel to slowly drip the magnesium acetate solution prepared in the previous step, and react for 1 hour after the addition is complete. Subsequently, 0.6 mol of triphenylguanidine is slowly dripped, and the reaction is carried out for 3 hours after the addition is complete. After the reaction is completed, vacuum filtration is performed to remove impurities in the precipitate. Subsequently, a rotary evaporator at 50 ° C is used for treatment for 2 hours to remove moisture and unreacted compounds. Finally, the sample is placed in a blast oven at 80 ° C and dried for 18 hours to obtain the final product Example 1.
[0046] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of Example 1 to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to completely disappear, add 50g of polyether polyol, continue stirring for 2 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 93mgKOH / g, acid value is 0.6mgKOH / g, and viscosity is 1970mPa·s (all physical properties are tested according to national standards).
[0047] Example 2
[0048] Take 1.3mol of nickel nitrate and dissolve it in deionized water to make a nickel nitrate solution for standby use. Take 0.7mol of 4-(hydroxymethyl)imidazole as a substrate in a 500ml three-necked flask and place it under 140°C for condensation reflux. At the same time, the nickel nitrate solution prepared in the previous step is slowly added dropwise using a constant pressure dropping funnel, and the reaction is performed for 2 hours after the addition is complete. Subsequently, 0.9mol of phenylethylamine is slowly added dropwise, and the reaction is performed for 2 hours after the addition is complete. After the reaction is completed, vacuum filtration is performed to remove impurities in the precipitate. Subsequently, a rotary evaporator at 60°C is used for treatment for 1 hour to remove moisture and unreacted compounds. Finally, the sample is placed in a 90°C blast oven and dried for 12 hours to obtain final product Example 2.
[0049] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of Example 2 to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to completely disappear, add 50g of polyether polyol, continue stirring for 2 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 87mgKOH / g, acid value is 0.6mgKOH / g, and viscosity is 2130mPa·s (all physical properties are tested according to national standards).
[0050] Example 3
[0051] Take 0.5 mol of zinc nitrate and dissolve it in deionized water to prepare a zinc nitrate solution for standby use. Take 0.4 mol of 6-hydroxymethylquinoline as a substrate in a 500 ml three-necked flask and place it under 120 ° C for condensation reflux. At the same time, use a constant pressure dropping funnel to slowly drip the zinc nitrate solution prepared in the previous step, and react for 1 hour after the addition is complete. Subsequently, 1 mol of sulfaguanidine is slowly dripped, and the reaction is carried out for 3 hours after the addition is complete. After the reaction is completed, vacuum filtration is carried out to remove impurities in the precipitate. Subsequently, a rotary evaporator at 60 ° C is used for treatment for 1 hour to remove moisture and unreacted compounds. Finally, the sample is placed in a blast oven at 80 ° C and dried for 24 hours to obtain the final product Example 3.
[0052] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of Example 3 to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to completely disappear, add 50g of polyether polyol, continue stirring for 2 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 76mgKOH / g, acid value is 0.6mgKOH / g, and viscosity is 4530mPa·s (all physical properties are tested according to national standards).
[0053] Example 4
[0054] Take 1.2 mol of zinc acetate and dissolve it in deionized water to prepare a zinc acetate solution for standby use. Take 1 mol of 2-hydroxymethyl-1-methylimidazole as a substrate in a 500 ml three-necked flask and place it under 150 ° C for condensation reflux. At the same time, use a constant pressure dropping funnel to slowly drip the zinc acetate solution prepared in the previous step, and react for 1 hour after the addition is complete. Subsequently, 1 mol of tetramethylguanidine is slowly dripped and reacted for 3 hours after the addition is complete. After the reaction is completed, vacuum filtration is performed to remove impurities in the precipitate. Subsequently, a rotary evaporator at 50 ° C is used for 2 hours to remove moisture and unreacted compounds. Finally, the sample is placed in an 80 ° C blast oven and dried for 18 hours to obtain the final product Example 4.
[0055] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of Example 4 to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to completely disappear, add 50g of polyether polyol, continue stirring for 2 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 65mgKOH / g, acid value is 0.6mgKOH / g, and viscosity is 1160mPa·s (all physical properties are tested according to national standards).
[0056] Table 1 Performance test results of products in various embodiments
[0057]
[0058] By comparing the physical properties of the recovered products of Examples 1-4 (see Table 1), it can be found that due to the same degradation formula, the main factors affecting the hydroxyl value and acid value are the type and content of the amine compound in the catalyst. From the viscosity of the recovered product, it can be found that the effect of Example 4 is the most beneficial. In order to better reflect the synergistic effect of the double anion catalyst, the formula in Example 4 is taken for further study, as follows.
[0059] The double anion catalyst example 4 (denoted as ZnA2) obtained in Example 4 was further analyzed. Figure 1 of 1 H NMR shows that the structure was successfully synthesized. The ICP-MS test results in Table 2 show that the Zn content in the product is 9.37%, so the product structure is inferred to be Figure 2 shown.
[0060] Table 2 ICP-MS test of ZnA2
[0061]
[0062] In order to demonstrate the synergistic effect of the double anion catalyst, the three individual components in the formula were used as catalysts and the experimental conditions were maintained for comparison. The scheme is as follows:
[0063] Comparative Example 1
[0064] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of zinc acetate to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to disappear completely, add 50g of polyether polyol, add 20g of succinic acid after continuous stirring for 2 hours, and increase the speed of mechanical stirring for continuous stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 65mgKOH / g, acid value is 0.7mgKOH / g, and viscosity is 3770mPa·s (all physical properties are tested according to national standards).
[0065] Comparative Example 2
[0066] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of 2-hydroxymethyl-1-methylimidazole to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After the waste polyurethane foam fragments disappear completely, add 50g of polyether polyol, continue stirring for 2 hours, then add 20g of succinic acid, and increase the speed of mechanical stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 59mgKOH / g, acid value is 1.3mgKOH / g, and viscosity is 5560mPa·s (all physical properties are tested according to national standards).
[0067] Comparative Example 3
[0068] First, add 10g of diethanolamine, 50g of polyether polyol and 3g of tetramethylguanidine to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to disappear completely, add 50g of polyether polyol, add 20g of succinic acid after continuous stirring for 2 hours, and increase the speed of mechanical stirring for continuous stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 71mgKOH / g, acid value is 1.5mgKOH / g, and viscosity is 7890mPa·s (all physical properties are tested according to national standards).
[0069] Comparative Example 4
[0070] First, add 10g of diethanolamine and 50g of polyether polyol to a 500mL three-necked flask, then turn on the mechanical stirrer and preheat at low speed and 180°C for 15 minutes. Next, increase the speed of mechanical stirring, and add 100g of waste polyurethane foam fragments into the three-necked flask by continuous feeding. After waiting for the waste polyurethane foam fragments to disappear completely, add 50g of polyether polyol, add 20g of succinic acid after continuous stirring for 2 hours, and increase the speed of mechanical stirring for continuous stirring for 2 hours until the basic physical properties of the degradation product do not change significantly. Its basic physical properties are as follows: hydroxyl value is 53mgKOH / g, acid value is 1.5mgKOH / g, and viscosity is 8900mPa·s (all physical properties are tested according to national standards).
[0071] Table 3 Performance test results of various embodiments and comparative examples
[0072]
[0073] The degradation products (recycled polyols) of the examples and comparative examples 1-4 were used to replace 30% of the original polyols to further prepare polyurethane soft foams. At room temperature of 25°C, the polyurethane foaming formula (Table 4) was used for foaming. The polyether polyols, the recycled polyols and the additives other than TDI were mixed with a high-speed stirrer at a speed of 9000r / min. At the same speed, TDI was quickly poured into the mold for mixing for 10-15 minutes and then foamed to prepare polyurethane foam. The prepared polyurethane foam was subjected to mechanical property tests to obtain the rebound rate, 50% permanent compression deformation rate, and 75% permanent compression deformation rate tests. The mechanical properties of the recycled foam are shown in Table 5:
[0074] Table 4 Polyurethane foaming formula
[0075]
[0076] Table 5 Mechanical properties of recycled foam
[0077]
[0078] Viscosity can reflect the degree of degradation of polyurethane to a certain extent. By comparing the physical properties of the recovered products of Example 4 (ZnA2) and Comparative Examples 1-4 (see Table 3), it is found that the viscosity of the degradation system with the addition of the di-anion catalyst ZnA2 is significantly reduced, and the degree of degradation is significantly improved. This shows that the catalytic effect of the synergistic effect of the di-anion catalyst is much higher than the effect of adding a certain component alone. Similarly, the performance data of the regenerated foam in Table 5 also reached the same conclusion, and the quality of the degradation product with the addition of the di-anion catalyst ZnA2 is much better than the degradation products of several other comparative examples. Therefore, the mechanical property data of the regenerated foam with the same recovery product addition amount reaching 30% is also improved. Therefore, the present invention is of great significance in the degradation of polyurethane and even the degradation of carbonyl-containing polymers, and is also of great significance for further realizing the industrialization of recycling of waste polyurethane.
[0079] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a dianionic catalyst, characterized in that: The following steps are involved: 1) dissolving a metal salt in deionized water to prepare a metal salt solution; 2) taking a nitrogen heterocyclic compound containing a hydroxyl group or an amino group as a substrate in a reactor, adding a metal salt solution dropwise to the reactor, and placing the reactor at 60° C. to 150° C. for condensation reflux for 1 to 8 hours; 3) adding an amine compound dropwise to the reactor after condensation and reflux in step 2), reacting for 2-5 hours after the addition is complete, and performing vacuum filtration after the reaction is complete to obtain a filtrate; 4) evaporating the filtrate obtained in step 3); 5) Drying the product obtained in step 4) to obtain a dianionic catalyst.
2. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 1), the metal salt is one or more of zinc acetate, magnesium acetate, zinc nitrate, cadmium nitrate, nickel nitrate and cobalt nitrate.
3. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 2), the nitrogen heterocyclic compound containing hydroxyl or amino group is one or more of 4-(hydroxymethyl)imidazole, 2-hydroxymethyl-1-methylimidazole, 6-(hydroxymethyl)pyridine-3-ol, 3,4-bis(hydroxymethyl)furan, and 6-hydroxymethylquinoline.
4. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 2), the metal salt solution is slowly added dropwise to the reactor, and the time for slowly adding the metal salt solution dropwise is 20-40 minutes.
5. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 2), the mixture is placed at 100° C.-150° C. for condensation reflux for 1-4 hours.
6. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 3), the amine compound is one or more of phenylethylamine, triphenylguanidine, tetramethylguanidine, and sulfaguanidine.
7. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 3), the amine compound is added dropwise to the reactor after condensation and reflux in step 2), and the mixture is reacted for 2-3 hours after the addition is completed.
8. The method for preparing a dianionic catalyst according to claim 1, characterized in that: The molar ratio of the nitrogen heterocyclic compound containing hydroxyl or amino group, the metal salt and the amine compound is 0.3-1: 0.3-1.5: 0.5-1.
9. The method for preparing a dianionic catalyst according to claim 1, characterized in that: In step 4), the filtrate obtained in step 3) is treated on a rotary evaporator at 50-60° C. for 1-2 hours; In step 5), the product obtained in step 4) is placed in a forced air oven at 80-90° C. and dried for 12-24 hours.
10. Use of the dianionic catalyst prepared according to the preparation method according to any one of claims 1 to 9 in catalytic degradation of polyurethane materials.
Citation Information
Patent Citations
Method for acidolysis of soft polyurethane foam waste to produce polyol
CN107286369A
Method for preparing polyether polyol by hydrothermal catalytic degradation of waste hard polyurethane material
CN110527136A
A method for efficient and controllable degradation and recycling of polyether polyols from polyurethane foam
CN113817221B
A method and device for degrading and recycling waste polyurethane foam
CN115260580B